Gender differences in the prevalence and clinical correlates of suicide attempts in young first-episode drug-naïve major depressive disorder patients with thyroid dysfunction - Luyu Liu; Jian Zhou; Xinran Song; Guowei Luo; Min Peng; Xiangyang Zhang (BMC Psychiatry)
Abstract Thyroid dysfunction is commonly seen in major depressive disorder (MDD), and is particularly prevalent in female patients. Moreover, gender differences occur in many aspects of MDD, including suicide attempts (SAs). We aimed to explore gender differences in the prevalence and clinical correlates of SAs in young first-episode drug-naïve MDD patients with thyroid dysfunction, which have not yet been reported. We recruited 509 patients in this study. Demographic and clinical characteristics were collected. We used HAMD-17, HAMA-14, the positive subscale of PANSS, and CGI-S to assess every participant. We found no significant difference in the prevalence of SAs between male and female subgroup. Gender differences in factors associated with SAs were found with anxiety, body mass index, serum anti-thyroid antibodies (A-TPO), and free triiodothyronine levels in male patients and anxiety, CGI-S score, and A-TPO in female patients. We found no gender differences in the prevalence of SAs; however, there were gender differences in several clinical correlates of SAs, highlighting specific strategies to avoid SAs in male and female MDD patients.